Mobility and data: cycling the utopian Internet of Things. Issue 1 (2nd January 2020) - Behrendt, Frauke
ABSTRACT: This article explores how cycling is currently considered in European policy documents related to transport aspects of the Internet of Things (IoT), what kind of representation of cycling can be imagined for utopian EC IoT policies documents, and how a combination of empirical policy analysis and a utopian approach could inform future policy and research. Debates around smart/intelligent/data mobilities and the IoT – including policy debates – tend to be dominated by motorized modes such as autonomous and networked cars. This article explores the implications of this for more sustainable and active modes such as cycling, both for current policies and for utopian thinking. It draws on literature concerned with utopian thinking, mobilities studies and critical data studies. The methodology combines a content analysis and a visual analysis of the EC policy documents with creating text and images for utopian future versions of these documents. The results show the heavy automotive focus of EC IoT policy documents and suggest an alternative bicycle-focussed IoT utopia. The conclusion facilitates a debate around utopian societies where smart cycling products, infrastructure, policy and funding facilitate sustainable, active and data-responsible mobility at scale. This challenges the current continuation of automobile cultures in smart mobility and IoT policy discourses, and the data and associated power asymmetries between cars and cycling that highlight the significance of this research.